Hyperbolic metamaterials and their applications. (March 2015) - Ferrari, Lorenzo; Wu, Chihhui; Lepage, Dominic; Zhang, Xiang; Liu, Zhaowei
Abstract: This review aims at providing a comprehensive and updated picture of the field of hyperbolic metamaterials, from the foundations to the most recent progresses and future perspectives. The topics discussed embrace theoretical aspects, practical realization and key challenges for applications such as imaging, spontaneous emission engineering, thermal, active and tunable hyperbolic media.